1997
DOI: 10.1095/biolreprod56.2.489
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Vascular Endothelial Growth Factor and Placenta Growth Factor in Human Placenta1

Abstract: Normal development and function of the placenta requires invasion of the maternal decidua by trophoblasts, followed by abundant and organized vascular growth. Little is known of the significance and function of the vascular endothelial growth factor (VEGF) family, which includes VEGF, VEGF-B, and VEGF-C, and of placenta growth factor (PIGF) in these processes. In this study we have analyzed the expression of VEGF and PIGF mRNAs and their protein products in placental tissue obtained from noncomplicated pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
141
0
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(150 citation statements)
references
References 27 publications
5
141
0
4
Order By: Relevance
“…PlGF mRNA was expressed in the trophoblast cells and its levels significantly increased as gestation advanced [7]. Vuorela et al [23] has showed that PlGF was expressed in the trophoblast cells of the human placenta, while this study focused on the expression of PlGF in placenta tissue of the streptozotocin-induced diabetic rat, where this study showed significant decreases in the expression levels of PlGF mRNA and protein.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…PlGF mRNA was expressed in the trophoblast cells and its levels significantly increased as gestation advanced [7]. Vuorela et al [23] has showed that PlGF was expressed in the trophoblast cells of the human placenta, while this study focused on the expression of PlGF in placenta tissue of the streptozotocin-induced diabetic rat, where this study showed significant decreases in the expression levels of PlGF mRNA and protein.…”
Section: Discussionmentioning
confidence: 91%
“…It is well accepted that the angiogenic growth factors VEGF and PlGF exist in placenta and act as important factors for placental development and fetal growth [8,23]. PlGF is abundantly expressed in the trophoblast cells of pla- centa [4,13,23]. We previously reported the expression and distribution of PlGF mRNA in the rat placenta at various gestational phases [7].…”
Section: Discussionmentioning
confidence: 99%
“…The main source of PGF during pregnancy is the placental trophoblast. It stimulates the proliferation, migration, and activation of endothelial cells (Vuorela et al 1997;Maglione et al 1991). Adiponectin is also reported to have angiogenic activity (Ouchi et al 2004) and therefore could be essential in the establishment of the vascular system in the ovary and potentially in the developing placenta, presumably by the stimulation of angiogenic factors, such as PGF.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the uNK cells can produce several cytokines and growth factors including placental growth factor (PlGF) [5,15]. PlGF is a member of the vascular endothelial growth factor (VEGF) [2,5], having crucial roles not only in the differentiation and migration of both endothelial and trophoblast cells [16], but also in placental growth [4,25] and fetal development during mid-late pregnancy [3]. However, it is not known whether diabetes may affect or alter the role and function of uNK cells at the feto-maternal interface.…”
mentioning
confidence: 99%
“…Prominent production of PlGF by trophoblast and the presence of Flt-1 receptors on trophoblast suggest that PlGF may act in an autocrine manner to modulate the trophoblast differentiation [23]. The uNK cells can also produce PlGF [3,4,24,25], suggesting that uNK cells may support the differentiation of endothelial cells together with VEGF. The present study also showed that PlGF protein did not change under diabetes condition, although PlGF mRNA expression was decreased.…”
mentioning
confidence: 99%